Analysis of Default on Illegal Online Loans in The Review of Civil Law and Islamic Law - Alsarandie, Fandi; Rizka, Rizka (IHSA Institute, 2024)
The development of information and communication technology has given birth to innovations in various fields, including the financial sector. One of the rapidly developing innovations is the emergence of online loans (pinjol). However, this pinjol has the potential for problems, one of which is the rise of illegal pinjol. This study aims to determine the process of agreements between online loan platforms and consumers, regulations and rights and obligations in agreements between online loan platforms and consumers according to civil law and Islamic law, and legal liability if one party defaults or violates the law. This research is a descriptive study with a normative research approach. The data sources for this study are secondary data and primary data. Data collection was carried out using literature studies and field studies (interviews). Furthermore, the data was analyzed using a qualitative approach. The results of this study show that the agreement process between illegal online loan platforms and consumers in Indonesia often does not meet the requirements for a valid contract regulated in the Civil Code, and violates the principles of consumer protection regulated in Law No. 8 of 1999. Agreements in online loan platforms, both according to civil law and Islamic law, must meet the requirements for a valid agreement which include agreement, capacity, clear objects, and lawful causes. In Islam, lending and borrowing must be done based on the principle of qardh which upholds mutual assistance and compliance with sharia. In the event of a default or violation of the law, especially in the context of illegal online loans, the agreement is invalid and null and void because it does not meet the requirements set out in Article 1320 of the Civil Code and does not comply with the principles of sharia law